Avaliação por Ngs das mutações de resistência nos genes da integrase, protease e transcriptase reversa do HIV-1 em indivíduos em falha virológica - Duro, Rodrigo Lopes Sanz [UNIFESP] (2017)
Introduction: With the introduction of Antiretroviral Therapy, there was an improvement in the quality of life in individuals with Human Immunodeficiency Virus. However, the selective pressure exerted by these drugs had a negative role in the treatment of these individuals, since they could select resistant viral strains that would lead to virological failure. With this, there was a need for the development of new drugs that had a better genetic barrier, capable of withstanding a greater number of mutations, these drugs are now used in salvage therapy. Another much discussed factor is minority mutations, not detected by the Sanger sequencing method, and that may interfere during the individual treatment. For this reason the use of NGS is important since it presents high coverage being able to detect these minority mutations. In this way we can evaluate the presence of majority and minority mutations for the third generation drugs used in salvage therapy. Objective: Evaluate the occurrence of HIV-1 Integrase, Protease and Reverse Transcriptase genes resistance mutations for Darunavir, Etravirine and Raltegravir salvage drugs in samples of HIV-positive patients in ART failure, in the city of São Paulo. Methods: Total of 147 subjects were analyzed, with CD4 <500 cells / mm 3, CV> 3.7 log / mL, age ≥18 years. Reaction Polymerase Chain was performed in the regions of Reverse Transcriptase, Protease and Integrase and was performed Massively Parallel Sequencing of these samples. Results: Mutations for the Integrase region (S147G, N155H and Q148H) were found for the Darunavir associated protein region (I47V, I54L, I84V, L33F, I50V, L33F, V32I, I54M and L76V) and the Reverse Transcriptase associated with Etravirine (L100I, K101P, M230L, Y181C and G190E). Minority resistance were found for the Protease region (M46I, I47V, F53L, I54L, V82A, I84V) for the Reverse Transcriptase region (M41I, K65R, D67N D67G, D67E, K70R, K70E, L74I, V75A, T215Y, K219N, L100I, K101P, K103S, Y188L, Y188S, P225H). Conclusion: Because resistance mutations associated with the Integrase region have been found this may be one of the few cases of transmitted resistance identified to date, since the individual did not use Integrase Inhibitors. The individuals in this study, because they were multi-experimented, had a large presence of mutations that would decrease the effectiveness of the Darunavir and Etravirine drugs even though they presented a greater genetic barrier than the other drugs. The minority mutations identified in this study have been shown to be a concern since mutations that would interfered with the susceptibility to salvage drugs have been identified and the presence of some TAMs has been identified.